(untitled) (Research, Society and Development, 2021)
Aiming to understand the motivation to study the mathematics and the disciplines associated with the natural sciences, this study focused on the theories of human behavior and nudges, to analyses the Robotics at School Program, of Recife’s City Hall. The methodology implemented was a bibliographic review, a documentary analysis of the project provided by the City Hall and a non-structured interview carried out with teachers from the Centro de Educação, Tecnologia e Cidadania (CETEC) and the Centro Comunitário da Paz (COMPAZ), which allowed the construction of a theoretical framework on the subject and an understanding of the wide scope of this project as it covers not only the municipal schools, but also the nursey schools and COMPAZ centers. As much as the Program is adapted to the reality of each space, it is possible to identify which aspects related to the theories of human behavior and nudges are present in its elaboration and implementation, from the moment when this action influences human behavior without any financial incentive. As it is offered on a public basis, without restricting freedom, as it is an optional subject, and offers the participant a greater possibility of having a choice nominated as ideal, which is to be a scholar.